Study on the Suitability of Mathematics Learning Media to Increase Interest of Vocational Students Through Media Learning Exhibition Activity - Rubono Setiawan; Henny Ekana Chrisnawati (Journal of Mathematics and Mathematics Education, 2023)
In this research, an evaluation was carried out to determine the suitability of different hands-on and digital learning tools designed to stimulate students' enthusiasm for mathematics, especially those in Vocational High Schools (SMK). These physical and digital educational resources were showcased during an exhibition, which was part of community engagement initiatives at SMK Warga Surakarta. During this event, a team of students and professors elucidated the functioning of these educational tools. Following this, math teachers from SMK, the intended users, provided assessments and analyses regarding the suitability of the demonstrated educational tools. Information collected from the exhibition, observations, validation records, and specifics about the educational tools were presented in a detailed and qualitative manner. Additionally, feedback for enhancements and advancements to elevate the quality of educational tools was gathered. Based on the qualitative descriptive analysis undertaken, both the physical and digital educational tools presented were deemed valid, fitting, and practical for the learning process, effectively augmenting students' interest.